Enhancing the Cultivation of Moina sp.: An integration of aeration system with green water detection and pH Monitoring - Baharom, Mohamad Faizal; Zakariah, Mohd Ihwan; Maslan, Mohd Nazmin; Saparudin, Faiz Asraf; Ambar, Radzi; Abdul Rahman, Shahnurriman (Wydawnictwo SIGMA-NOT, 2024)
Moina sp., a zooplankton with high protein content, serves as a vital live fish meal for aquatic species, including Betta spp. fry. Nevertheless, the cultivation of this particular species poses challenges due to its limited lifespan and inadequate water requirements. Focusing to address this issue, the proposition of an inventive framework for water parameter monitoring to utilize pH and temperature sensors was applied. The detection of green algal blooms is facilitated by an artificial intelligence-driven computer vision system, which effectively notifies individuals using Blynk applications. The implementation of this partially automated technique enhances the efficiency of Moina production, hence meeting the requirements of the aquaculture industry. Significantly, this represents the inaugural Moina Aeration System (MAS) that incorporates Internet of Things (IoT) integration.